2013
DOI: 10.15376/biores.8.3.3189-3199
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Surface Roughness of Heat-Treated Wood Materials Planed by the Cutters of a Horizontal Milling Machine

Abstract: The aim of the present study was to determine the surface roughness of heat-treated Scots pine (Pinus sylvestris L.), Eastern beech (Fagus orientalis L.), Uludağ fir (Abies bornmülleriana Mattf.), and sessile oak (Quercus petraea L.) wood material samples following planing by the cutters of a horizontal milling machine. The samples that were heattreated at 140 ºC or 160 ºC for 3, 5, or 7 hours were then processed by star blades or razor blades, which are the most frequently used blade types in a milling machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 12 publications
1
25
1
5
Order By: Relevance
“…Hendarto et al (2006) determined the effect of various methods of the surface Ra evaluation and the changes in values between methods depending on the filtration used and partial difference of certain methods. The conclusions of the research by Budakçı et al (2013) indicated that the laser method is more suitable for determining the surface quality than the contact method. Table 8 shows an evaluation of the effect of factors on the surface Ra measured by the contactless method using Duncan's test.…”
Section: Resultsmentioning
confidence: 99%
“…Hendarto et al (2006) determined the effect of various methods of the surface Ra evaluation and the changes in values between methods depending on the filtration used and partial difference of certain methods. The conclusions of the research by Budakçı et al (2013) indicated that the laser method is more suitable for determining the surface quality than the contact method. Table 8 shows an evaluation of the effect of factors on the surface Ra measured by the contactless method using Duncan's test.…”
Section: Resultsmentioning
confidence: 99%
“…A capacidade para quantificar e controlar a rugosidade da superfície, que varia em larga escala, como resultado das diferenças metodológicas no processamento da madeira utilizando ferramentas ou máquinas, é muito importante em várias aplicações (Yildiz, 2002). Cada objeto tem uma superfície composta por picos e vales em miniatura e a distribuição dimensional e de área desses picos e vales afeta as propriedades da superfície (Budakçi et al, 2013).…”
Section: Introductionunclassified
“…Knowing the cutting power, it is then easy to determine the cutting force, which is understood as the force that has to be exerted on the machining tool in order to overcome the resistance of the wood and perform the chip-forming process (Budakçı et al 2013;Novak et al (2011);Lesko 2004) (Eq. 2)…”
Section: Introductionmentioning
confidence: 99%